Body mass index (BMI) does not predict responses to psilocybin - Spriggs, Meg; Giribaldi, Bruna; Lyons, Taylor; Rosas, Fernando E; Kärtner, Laura; Buchborn, Tobias; Douglass, Hannah M; Roseman, Leor; Timmermann, Christopher; Erritzoe, David; Nutt, David J; Carhart-Harris, Robin L (Journal of psychopharmacology, 2023)
Background: Psilocybin is a serotonin type 2A (5-HT2A) receptor agonist and naturally occurring psychedelic. 5-HT2A receptor density is known to be associated with body mass index (BMI), however, the impact of this on psilocybin therapy has not been explored. While body weight-adjusted dosing is widely used, this imposes a practical and financial strain on the scalability of psychedelic therapy. This gap between evidence and practice is caused by the absence of studies clarifying the relationship between BMI, the acute psychedelic experience and long-term psychological outcomes. - Method: Data were pooled across three studies using a fixed 25 mg dose of psilocybin delivered in a therapeutic context to assess whether BMI predicts characteristics of the acute experience and changes in well-being 2 weeks later. Supplementing frequentist analysis with Bayes Factors has enabled for conclusions to be drawn regarding the null hypothesis. - Results: Results support the null hypothesis that BMI does not predict overall intensity of the altered state, mystical experiences, perceptual changes or emotional breakthroughs during the acute experience. There was weak evidence for greater ‘dread of ego dissolution’ in participants with lower BMI, however, further analysis suggested BMI did not meaningfully add to the combination of the other covariates (age, sex and study). While mystical-type experiences and emotional breakthroughs were strong predictors of improvements in well-being, BMI was not. - Conclusions: These findings have important implications for our understanding of pharmacological and extra-pharmacological contributors to psychedelic-assisted therapy and for the standardization of a fixed therapeutic dose in psychedelic-assisted therapy.